[Untitled article] - Gagné, Jean-H. (Relations industrielles / Industrial Relations, 1951)
SummaryThe awards studied under this heading were rendered during the months of August, September and October of this year and represent more than 25 decisions. An outline of the points which we found to be of the most interest in these awards follows, under the various subjects covered.